Pengaruh Kebersihan Lingkungan Sekolah terhadap Kenyamanan Belajar Anak di Paud KB IPB - Ayu Safitri; Nurinda Rahim Doe; Apriliawati Lahabu; Fitrianti Yakob Ibrahim; Wahyuni Ngabito (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2026)
This study aims to determine the relationship between family social support and the discipline of 4-5-year-old children at Pembina State Kindergarten. The study used a quantitative method with a descriptive correlational approach. A sample of 14 parents was selected using a purposive sampling technique. Data were obtained through a five-level Likert scale questionnaire and analyzed using the Pearson Product-Moment correlation test. The results showed that children's discipline was in the very high category at 93.5%, while family social support was also in the very high category at 94.9%. However, the correlation test showed an r value of –0.14, indicating a very weak and insignificant relationship between family social support and children's discipline. This finding indicates that, despite high family support, other factors such as role models and school habits likely have a greater influence on the development of children's discipline. This study emphasizes the importance of collaboration between families and educational institutions in supporting the development of discipline in early childhood.